Punctuation in the western writing system - Rocha, Iúta Lerche Vieira (2019)
This overview article undertakes a survey of the punctuation system in the West from both diachronic and synchronic points of view. Punctuation is defined as the system of graphic signs developed through the centuries as complementary to the Greeks and Latins. With invention of the printing in the Middle Ages, the diffusion of the complementary system received and additional impetus whose impact is felt even today. An examination of the Portuguese graphic system is followed by a discussion of its complexity as well as its internal contradictions. the graphic-spatial aspects of punctuation are also discussed, alongside the problem of pagination.